Development of sustainable downstream processing for nutritional oil production - Rollin, Samuel; Gupta, Adarsha; Franco, Christopher M. M.; Singh, Surinder; Puri, Munish (Frontiers in Bioengineering and Biotechnology, 2023)
Nutritional oils (mainly omega-3 fatty acids) are receiving increased attention as critical supplementary compounds for the improvement and maintenance of human health and wellbeing. However, the predominant sources of these oils have historically shown numerous limitations relating to desirability and sustainability; hence the crucial focus is now on developing smarter, greener, and more environmentally favourable alternatives. This study was undertaken to consider and assess the numerous prevailing and emerging techniques implicated across the stages of fatty acid downstream processing. A structured and critical comparison of the major classes of disruption methodology (physical, chemical, thermal, and biological) is presented, with discussion and consideration of the viability of new extraction techniques.Owing to a greater desire for sustainable industrial practices, and a desperate need to make nutritional oils more available; great emphasis has been placed on the discovery and adoption of highly sought-after 'green' alternatives, which demonstrate improved efficiency and reduced toxicity compared to conventional practices. Based on these findings, this review also advocates new forays into application of novel nanomaterials in fatty acid separation to improve the sustainability of nutritional oil downstream processing. In summary, this review provides a detailed overview of the current and developing landscape of nutritional oil; and concludes that adoption and refinement of these sustainable alternatives could promptly allow for development of a more complete 'green' process for nutritional oil extraction; allowing us to better meet worldwide needs without costing the environment.